2020
DOI: 10.1136/postgradmedj-2020-137840
|View full text |Cite
|
Sign up to set email alerts
|

Continuing medical education during a pandemic: an academic institution’s experience

Abstract: The COVID-19 pandemic has affected healthcare systems worldwide. The disruption to hospital routines has affected continuing medical education (CME) for specialty trainees (STs). We share our academic institution's experience in mitigating the disruption on the CME programme amidst the pandemic. Most specialty training programmes had switched to videoconferencing to maintain teaching. Some programmes also utilized small group teachings with precautions and e-learning modules. Surgical residencies were dispropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 11 publications
4
72
0
14
Order By: Relevance
“…Zoom is an innovative meeting company that unifies cloud WVC, simple web meetings, and group collaboration in one easy-to-use platform. It has been one of the most extensively used tools for facilitating ongoing synchronous educational activities during the COVID-19 pandemic [ 24 , 25 ]. Furthermore, it allows wireless screen and whiteboard sharing, has an interactive chat room, and is free for up to 40 min.…”
Section: Methodsmentioning
confidence: 99%
“…Zoom is an innovative meeting company that unifies cloud WVC, simple web meetings, and group collaboration in one easy-to-use platform. It has been one of the most extensively used tools for facilitating ongoing synchronous educational activities during the COVID-19 pandemic [ 24 , 25 ]. Furthermore, it allows wireless screen and whiteboard sharing, has an interactive chat room, and is free for up to 40 min.…”
Section: Methodsmentioning
confidence: 99%
“…In Asia, studies reported government enforced lockdowns and restrictive measures, including the closure of medical campuses (Singh et al 2020;Srinivasan 2020;Veasuvalingam and Goodson 2020). Studies in Singapore reported the escalation of the national pandemic alert to Disease Outbreak Response System Condition (DORSCON)-Orange resulting in quarantining, temperature screenings and visitor restrictions at hospitals (Boursicot et al 2020;Kanneganti et al 2020;Samarasekera et al 2020). In Europe, countries implemented national restrictions on non-essential activities, invoked lockdowns and moved all educational activities online (Finn et al 2020;Moszkowicz et al 2020;Torres et al 2020).…”
Section: Geographical Location and Local Covid-19 Specific Detailsmentioning
confidence: 99%
“…Zoom is an innovative meeting company that uni es cloud WVC, simple web meetings, and group collaboration in one easy-to-use platform. It has been one of the most extensively used tools for facilitating ongoing synchronous educational activities during the COVID-19 pandemic [24,25]. Furthermore, it allows wireless screen and whiteboard sharing, has an interactive chat room, and is free for up to 40 minutes.…”
Section: Video Conferencing Session Administrationmentioning
confidence: 99%